Pembatasan Kasasi Perkara Pidana Oleh Mahkamah Agung Ditinjau Dari Hak Rakyat Untuk Memperoleh Keadilan - Aurelia Verina Withania; Ahmad Mahyani (UIN Syarif Hidayatullah Jakarta, 2021)
The existence of rules limiting the cassation becomes an obstacle for the public to obtain justice and is not in accordance with the principles of the state of Indonesia as a state of law which is stated in the provisions of the 1945 Constitution of the Republic of Indonesia in Article 28D. Problem: Is the limitation of cassation in Article 45A of the Supreme Court Law in accordance with the provisions of the 1945 Constitution and the Criminal Procedure Code. This research is a normative research method with a statutory approach and a conceptual approach as well as prescriptive analysis techniques. The cassation legal effort should return to its basic purpose, namely maintaining legal uniformity and unity and providing justice for the community.